AN EPISTEMOLOGICAL BASIS FOR CROSS CULTURAL UNDERSTANDING (2014)
Many of the conflicts in the world today, in the areas of politics, religion and ethnicity, are reflections of a dearth of understanding among cultures. Several studies have identified the need for cross cultural understanding and tried to establish a basis for it in human biological make up, the universality of emotions and lived experience. However, these attempts have not satisfactorily addressed the universal epistemological basis for cross cultural understanding, the absence of which has caused social conflicts to persist. This study, therefore, provided an epistemological foundation for cross cultural understanding in terms of the relationship between basic beliefs and non-basic beliefs, with a view to facilitating a resolution of the conflicts generated by cross cultural misunderstanding. This study adopted aspects of Donald Davidson’s theory of triangulation. This theory states that two persons from different cultures cannot have incommensurate basic belief about an object, if the same object serves as the origin of the belief as well as a basis for justifying the belief state. Relevant core texts in Philosophy of Culture (5), Epistemology (5) and Political Philosophy (5) were purposively selected. The analytical, critical and reconstructive methods of philosophy were employed in this study. The analytical method helped in clarifying concepts like culture, understanding, epistemology, belief and universality of emotions that form the basis for cross cultural understanding. The critical method was employed to examine earlier positions on cross cultural understanding and the method of reconstruction was adopted to establish an epistemological basis for it. Texts on Philosophy of Culture revealed that cultural incommensurability is not tenable in the light of universal human rights advanced by universalists though they fail to define the element in human nature that constitute the foundation for cross cultural understanding. Works on Epistemology showed that universality of emotions is problematic because existence transcends emotion. The universalists have not explained what qualifies as lived experience, hence, the need for an epistemological variable of belief. Beliefs form the basis for cultural overlaps because they are elicited by common objects in the world. Materials on Political Philosophy revealed the imperativeness of peace in human society. Belief interconnectedness was expressed in the condemnation of genocide in Rwanda and the extermination of Jews by Nazis. Critical interrogation showed that belief overlap is justified by common objects. Given that beliefs overlap, cross cultural understanding is possible. It is basic belief about common nature, need for justice and transcendence and not non-basic beliefs like religion and ideology that make cross cultural understanding possible contrary to the position of cultural relativists. Cross cultural conflicts result from holding too rigidly to the dictates of relativism in forms of life to the neglect of the overlap of universal, basic or primary beliefs which constitute viable factors in the resolution of conflicts among cultures. Recognition of overlap of primary beliefs between cultures serves as the main basis for facilitating the resolution of conflicts engendered by cross cultural misunderstanding. Therefore, a universalist epistemology of beliefs constitutes an essential basis for cross cultural understanding.